MANAJEMEN RISIKO PEMBIAYAAN MUDHARABAH PADA PERBANKAN SYARIAH - Indrianawati, Indrianawati; Lailah, Nisful; Karina, Dewi (Faculty of Economics and Business, University of Muhammadiyah Malang, 2015)
The purpose of this research is to determine risk management of mudharabah financing in Islamic banking limited to the causes of the low number of mudharabah financing, the common problems and solutions. The method of the research is using a qualitative approach with a case study strategy. The informants are obtained from 3 Islamic Banks (BUS), namely BMI, BSM and BNI Syariah. The data collection is conducted by combining the questions and the obtained data with the result of interview with the Account Officer from the 3 Islamic Banks; BMI, BSM, and BNI Syariah. The result of the research showed that the low number of mudharabah financing is caused by the massive risk, particularly the risk of losses on the bank income. Meanwhile, the problems that commonly occur are non-performing financing because of the side streaming and manipulated data. The solution is restructuring to the bank’s customer who has a good faith. In contrast, bank’s customers that have no good willing to fulfill their obligation will be put into the insurance execution.